PARTICIPATION OF LEGAL ENTITIES IN INTERNATIONAL ECONOMIC RELATIONS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article explores the dynamic role of legal entities in the context of international economic relations. As globalization continues to reshape the business landscape, legal entities play a crucial role in facilitating cross-border transactions, fostering international trade, and navigating complex legal frameworks. The study examines the literature on the subject, analyzes the methods employed by legal entities in international economic activities, presents key results, and engages in a discussion on the implications for the global business environment.